PERAN POLA ASUH ORANG TUA DALAM PENANAMAN RASA CINTA TANAH AIR DAN BUDAYA PADA ANAK USIA DINI - Dhinanda Aulia; Indah Khairani Hasibuan; Khairani Munadia; Masganti Sitorus (LPPM IAD Probolinggo, 2024)
This study aims to analyze the role of parenting on the cultivation of the value of love for homeland and local culture in early childhood. In the era of globalization that brings foreign cultural influences, the role of parents as educators at home is very important. Through a qualitative approach and literature study, this research found that democratic parenting is more effective in building children's sense of attachment to their culture, through involvement in discussions and direct experience. In contrast, authoritarian and permissive parenting can hinder children's understanding of cultural values and reduce their love for their homeland. The results of this study emphasize the importance of creating a balanced, loving environment and providing clear guidance so that children can grow into individuals who are proud of their cultural identity. Thus, parents are expected to implement parenting patterns that support the cultivation of national and cultural values in the next generation. Keywords: Parenting, Love for the Country, Local Culture. Early Childhood, Cultural Identity